HYPROP measurements of the unsaturated hydraulic properties of a carbonate rock sample - Lipovetsky, Tatiana; Zhuang, Luwen; Teixeira, Wenceslau G.; Boyd, Austin; May Pontedeiro, Elizabeth; Moriconi, Luca; Alves, José L.D.; Couto, Paulo; van Genuchten, Martinus Th. [UNESP] (Elsevier, 2020)
The unsaturated hydraulic properties provide important theoretical and practical information about fluid flow in soils and rocks for a range of soil, environmental and engineering applications. In this study we used the evaporation (HYPROP) and chilled-mirror dew point (WP4C) methods to estimate the water retention and unsaturated hydraulic conductivity curves of an Indiana Limestone carbonate rock sample. The obtained data were analyzed in terms of unimodal and bimodal VG (van Genuchten, 1980) and PDI (Peters et al., 2015) type functions. Bimodal functions were found to produce excellent descriptions for the unsaturated hydraulic data we measured, slightly better than the standard unimodal formulations. For our particular test using an Indiana Limestone rock sample, we did not find much improvement when accounting for film and corner flow using the PDI formulation, relative to the VG model. As far as we know, this is the first time the HYPROP methodology was applied to a rock sample.
Keywords: Bimodal hydraulic functions; Carbonate rock; HYPROP evaporation method; Unsaturated hydraulic Properties; WP4C